2008
DOI: 10.1007/s00128-008-9361-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation of Trace Elements in Waters Polluted by Municipal Solid Waste Landfill Leachate

Abstract: Landfill leachate-polluted stream waters were monitored in three sampling campaigns (November 2001 to June 2006), with emphasis on trace elements. The data were evaluated by means of statistics and speciation modelling. Two statistically different groups of trace elements were distinguished: (1) Ba, Sr, Al, Fe, Mn, Cr, Co, Ni, V, As, Se, Sb, U, Li, Rb and Cs decrease during the rain event due to dilution; (2) Pb, Zn, Cu and Cd increase during the rain event due to the dissolution of hydrous ferric oxides and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 11 publications
(22 reference statements)
2
16
0
2
Order By: Relevance
“…The samples from the closed landfill at Dolní Chabry (CH) were taken from tubes draining the leachate from the landfill body and conducting it directly to a small stream. More information on this landfill site is also given in our previous publications [7,9].…”
Section: Leachate Samplingmentioning
confidence: 97%
See 1 more Smart Citation
“…The samples from the closed landfill at Dolní Chabry (CH) were taken from tubes draining the leachate from the landfill body and conducting it directly to a small stream. More information on this landfill site is also given in our previous publications [7,9].…”
Section: Leachate Samplingmentioning
confidence: 97%
“…In particular, metals (Pb, Cu, Zn, Cd and Ni) in landfill leachates have been found to be associated with colloidal particles of various sizes influencing their speciation, mobility and toxicity [4][5][6]. In our previous paper focused on long-term monitoring of landfill leachates [7], we showed that attention should also be devoted to other trace elements, and not only to metals. Binding of trace elements to colloids can have important implications for selection of the most efficient method for the landfill leachate treatment [8] and for evaluation of trace element mobility in the case of leakage from the landfill body into the surrounding environment [6].…”
Section: Introductionmentioning
confidence: 97%
“…The landfill drainage layer is required as a filter, which helps with reducing the risk in surrounding landfill areas. One of the widely concerning problems dealing with the drainage layer is using recyclable materials for drainable formation [21]. Construction wastes are not applied for the drainage layer because of a high content of calcium carbonate, which increases the possibility of clogging processes.…”
Section: Introductionmentioning
confidence: 99%
“…Applied nature of these programs involves testing the impact on the embryogenesis of each substance alone (FETAX, 1991), although in nature, in the embryo affects a complex of pollutants of the lake. Therefore, in recent years, within the confines of FETAX system, are conducted analyzes of the synergistic complex of pollutants (Orton et al, 2006;Ettler et al, 2008), which allows to evaluate the natural biotoxicity and anthropogenic pollutants.…”
Section: Introductionmentioning
confidence: 99%